Um breve apanhado da técnica de imersão na história da cinematografia - Aly, Natália (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article aim to locate the technical history of cinematography technological advances focused to search for immersion. Considering that the film and its experimentations gave up strongly in avant-garde movements, was through this period of investigation that cinematic image has spawned a remarkable experimental roots to the present day. Even outside of the big commercial film circuit, is currently a noticeable influence on the works of such period on contemporary research. When developing an expansion of technological cinematography out of the mold of classic cinema and more precisely in the context of digital era, tools are created clearly rooted in the experimental context and the scientific discoveries, inevitably intricate sensory and immersive environments.